Promotion of Chinese TV Series in Russia: Key Factors - Jiamei Song; Lin Xi (RUDN Journal of Studies in Literature and Journalism)
In the context of increasing globalization, national audiovisual content is becoming an important tool for intercultural communication. The cultural exchange between China and Russia is marked by the growing interest in Chinese TV series in Russia, while the mechanisms of distribution of Chinese television series in the Russian market have not been reflected in the scientific field. The authors have identified specific strategies for promoting Chinese content and analyzed the perception of Chinese TV series by the Russian audience. The study was conducted in the context of China’s foreign cultural policy using Russian empirical data. The results demonstrate that the distribution of Chinese TV series in Russia largely depends on Chinese government support aimed at strategically promoting TV products abroad, as well as the use of a multi-channel content distribution model. This model includes the synergy of Chinese and Russian television channels, local streaming platforms, social networks, and international video services. This approach contributes to the progressive strengthening of the Chinese presence in the Russian media sphere and strengthening its influence on the Russian market. An analysis of data from the KinoPoisk portal shows a growing interest in Chinese TV series, which is reflected in an increase in the number of ratings and reviews, and high ratings. The key factors in genre and content policy are related to marketing aspects: responding to audience expectations, genre diversification, an emphasis on melodramas, fantasy and action films, and high-quality content. The authors offer counter recommendations for the promotion of television content in China, which can serve as a guideline for the effective distribution of Russian video products based on Chinese-Russian cultural cooperation.